The Efforts of Students at SMP Negeri 2 Semarang to Improve Music Learning Outcomes Through Learning Media - Maulana Resha Vivadi; Lukas Gunawan Arga Rakasiwi (Jurnal Seni Musik, 2024)
Media is a component of education that functions to improve student learning outcomes. The use of media by students is closely related to their level of study and the topics being learned. Therefore, the selection and effort made by students in utilizing media can significantly impact their learning achievements. This study aimed to identify, describe, and analyze the types of media used by students and their efforts in utilizing these media to enhance their learning outcomes. This study employed descriptive quantitative method complemented by qualitative research procedures. The sample consisted of seventh-grade students from SMP Negeri (State Junior High School) 2 Kota Semarang. Data collection techniques included observation, questionnaires, structured interviews, and document studies. Descriptive statistical analysis was conducted using IBM SPSS Statistics version 25, followed by an interactive model comprising data collection, data reduction, data presentation, and data verification. The results show that 68% of seventh-grade students are familiar with various forms of media, and 67% have already used them. One of the media used by these students is musical instruments. Seventh-grade students use media with the aim of enhancing their learning outcomes. In terms of academic achievements in music, seventh-grade students demonstrated improvement, as evidenced by an increase in the average midterm exam score from 81.3518 to 85.5276 by the end of the semester. The most frequent midterm score of 75.00 rose to 83.00 by the end of the semester. These findings suggest that the use of educational media can indeed enhance learning outcomes in music for seventh-grade students.